The Farm and Ranch Guide to Environmental Auditing - Michael T. Olexa; Regina Fegan (EDIS, 2002)
This is EDIS document AS927, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published June 2002.